Comparación de población urbana y rural con infarto transmural al miocardio en la provincia del Biobío, Región del Biobío, Chile - Mallol S., Manuel; Domínguez L., Aníbal; Meza F., Estefanía (Revista Hospital Clínico Universidad de Chile, 2024)
One of the main causes of death in Chile and the world are cardiovascular diseases. Multiple strategies seek to reduce them, with local epidemiology becoming relevant for that. Objectives: To describe the demographic and clinical characteristics of rural and urban patients with ST-segment elevation myocardial infarction (IMEST) in the province of Biobío. Methods: A prospective registry was made of all patients admitted for IMEST between October 2019 and October 2020. Results: 100 records were obtained. 32% corresponded to rural population and 68% to urban population (p <0.001). The age in urban patients was lower than rural ones (58.9 vs 66.5 years, p<0.05). For both groups, the predominant sex was male. Smoking was higher in the urban population (51.4 vs 31.2%, p<0.05). LDL cholesterol was lower in the rural population (106 vs 122.7mg / dL, p<0.05). There was no difference in ischemia time, diabetes, HDL, reperfusion and mortality. Conclusions: A third of the study population were rural patients, with epidemiological profile different from the urban ones. That may be related to lifestyle habits that condition the above. Our study